Awareness, attitude and practice of contraception among antenatal women in a tertiary care hospital- a cross sectional study - Murugesan, Anuradha; Sundaram, Ramya; Muthusamy, Muthulakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Reproductive health services that empower women will greatly reduce the social and economic disruption in society. The aim of the study was to assess the level of awareness about different types of contraceptive choices and also to find out the current practice of contraceptive methods by antenatal women attending the antenatal outpatient department in a tertiary care hospital. Methods: This was a cross-sectional study conducted over a period of 6 months at SRM medical college hospital. 200 antenatal women attending outpatient department of obstetrics and gynecology were randomly selected and were interviewed with predesigned questionnaire. The data collected were analysed using percentage. Results: Majority of the women in the study were between 20 to 25 years. 97% were aware of contraception, 81% were aware of the needs of birth spacing and only 64% were aware of the benefits of birth spacing methods. About 74% of them were aware of more than one method of contraception. Condom (93%) was the most heard about method. Only 23% of these women gave a history of usage of contraception. Majority of these women had used condoms (16%). Sterilisation (44%) was considered the safest option among the contraceptive choices followed. Social circle (49%) and health care providers (42%) played a major role as source of knowledge. Majority of the antenatal women did not use contraception because of desire of child (41%) and fear of side effects (21%). Conclusions: The high contraceptive awareness and educational level did not reflect on the contraceptive usage level in this study. Hence proper counselling and education is required to motivate the women for contraceptive usage and eradication of myths involving the risks of using contraception.